De Novo Sequencing and Analysis of Lemongrass Transcriptome Provide First Insights into the Essential Oil Biosynthesis of Aromatic Grasses - Meena, Seema; Kumar, Sarma R.; Venkata Rao, D. K.; Dwivedi, Varun; Shilpashree, H. B.; Rastogi, Shubhra; Shasany, Ajit K.; Nagegowda, Dinesh A. (Frontiers in Plant Science, 2016)
Aromatic grasses of the genus Cymbopogon (Poaceae family) represent unique group of plants that produce diverse composition of monoterpene rich essential oils, which have great value in flavour, fragrance, cosmetic and aromatherapy industries. Despite the commercial importance of these natural aromatic oils, their biosynthesis at the molecular level remains unexplored. As the first step towards understanding the essential oil biosynthesis, we performed de novo transcriptome assembly and analysis of C. flexuosus (lemongrass) by employing Illumina sequencing. Mining of transcriptome data and subsequent phylogenetic analysis led to identification of terpene synthases (TPS), pyrophosphatases (PPase), alcohol dehydrogenases (ADH), aldo-keto reductases (AKR), carotenoid cleavage dioxygenases (CCD), alcohol acetyltransferases (AAT) and aldehyde dehydrogenases (ALDH), which are potentially involved in essential oil biosynthesis. Comparative essential oil profiling and mRNA expression analysis in three Cymbopogon species (C. flexuosus, aldehyde type; C. martinii, alcohol type; and C. winterianus, intermediate type) with varying essential oil composition indicated the involvement of identified candidate genes in the formation of alcohols, aldehydes and acetates. Molecular modeling and docking further supported the role of identified enzymes in aroma formation in Cymbopogon. Also, simple sequence repeats (SSRs) were found in the transcriptome with many linked to terpene pathway genes including the genes potentially involved in aroma biosynthesis. This work provides the first insights into the essential oil biosynthesis of aromatic grasses, and the identified candidate genes and markers can be a great resource for biotechnological and molecular breeding approaches to modulate the essential oil composition.